Analisis Isi Konten Youtube (Bloom Media) “Membahas Masalah Mental Health Generasi Strawberry” - Rhizqi Dwiputra Ramadhan; Arfian Suryasuciramdhan; Agil Hari; Firdy Ahmad Fariji; Refky Genta Saputra (Institut Nalanda, 2024)
Gen-Z is a generation that is very spoiled by technology and the internet. The way they think and live their lives is different from previous generations. Generation Z is often referred to as the